Reframing curriculum and pedagogical discourse in Universities of Technology - Ntshoe, Isaac (South African Journal of Higher Education, 2016)
This articles aims to demystify curriculum and pedagogical discourses and related practices of sectoral occupational fields and qualifications of universities of technology (UoTs). The article takes issue with the academic tradition which emphasises distinctiveness of UoT as a sector that should focus exclusively on applied knowledge that is fixed to practice. This I do by exploring unconventional theoretical and conceptual epistemes to undergird curricula and pedagogic discourses in UoTs. The article makes a case for a conscious shift towards a knowledge-based approach to embed offerings, curriculum, pedagogy, teaching, learning and assessment. I argue that the current emphasis on the applied knowledge devoid of conceptual knowledge base and the principle of matching in UoTs is one-dimensional. I further argue that competence-and outcomes-based models have inherent shortcomings to drive curriculum change, and therefore propose the conceptual and contextual approach to strengthen the knowledge base of offering and programmes of UoTs. Key words: specialised knowledge; curriculum and pedagogy; conceptual and contextual; universities of technology.